Dysphagia New Advances - Ahmed, Monjur (IntechOpen, 2022)
This book gives an update on the management of dysphagia due to a variety of disorders. Chapters address management of dysphagia due to corrosive ingestion and following anterior cervical surgery, nutritional, endoscopic, and surgical management of dysphagia, the role of surgery in patients with advanced achalasia, dysphagia in patients with head and neck cancer, and lipofilling and oral neuromuscular treatment.